KEJAHATAN LINGKUNGAN HIDUP (SUATU KAJIAN KRIMINOLOGIS TERHADAP BERLAKUNYA UU LH) - SUSILAWATI, ENDANG YULIANA (Wacana Hukum, 2009)
Abstract:Ecology is the first and the main sources for human necessity. Therefore, laws are made to ensure its sustainability. One of the efforts is to provide penalty for those who disobey. However, there  still much disobedience. Keywords: law renewing and progressive law